Bending time: lessons from critical, community-engaged, liberatory research - Lozenski, Brian D.; Chikkatur, Anita P. (Frontiers in Research Metrics and Analytics, 2023)
In this article, we use the framework of chronopolitics and racialized time (Cooper, 2017; Mills, 2020) to explore our experiences as professors of color at predominantly white institutions who strive to do emancipatory, community-driven research. Our shared work as organizers for EdLibMN, a grassroots organization working to bring together various constituencies in Minnesota to organize for educational justice, led us to think together about chronopolitics as a framework to understand how our scholarly commitments to social transformation and liberatory education impact our labor and teaching practices at our institutions. This framework allows us to examine our relationships with communities in our individual research and advocacy contexts as well as in our shared work as organizers for EdLibMN. In particular, we explore how the urgency and timeline of our community-based advocacy work and the rhythms and improvisation of participatory action research are juxtaposed with the surveillance and evaluation of our labor and the urgency of “tenure clocks” at our institutions. We end by discussing our own transformational learning through our collaborations with community researchers and organizers. We speculate about the possibilities of bending time--the chronopolitics of collective struggle and joy--that allows us to focus on building relationships as a central tenet of emancipatory research practices and to ensure our own health and well-being as scholar-activists of color.